Plasmodium Species Infections In Children Suspected Of Malaria At Yendi Municipal Hospital, Northern Region - Manda, L. (University of Ghana, 2017)
Background: Rapid diagnostic tests (RDTs) are now widely used in health facilities in Ghana. However, there is a possibility that the use of RDTs specific to Plasmodium falciparum may lead to missed diagnosis of non-falciparum species and mixed infections. Ghana is still in the control phase of malaria and poor knowledge of caregivers about malaria can negatively impact on malaria control interventions in children. Therefore, the study determined the prevalence of Plasmodium species and factors associated with malaria transmission in children suspected of malaria. The study also assessed knowledge, attitudes and practices (KAP) of caregivers on malaria prevention and control in children. Methods: A cross-sectional study was undertaken at Yendi Municipal Hospital in Northern Region of Ghana and 338 children suspected of malaria were enrolled. Thick and thin smears were prepared from capillary blood of the children, then stained with Giemsa and read under a light microscope. A case report form was used to interview each caregiver of the children who gave consent in local languages understandable by them. Data were entered in Microsoft Excel and analyzed using STATA version 14. Results: The prevalence of Plasmodium falciparum was 17.2% (58/338). No mixed infection and gametocyte was found in the children. Age and gender of children had no significance difference in relation to malaria (p>0.05). Gender of caregiver, marital status, education level and occupation were not associated with malaria infections in children (p>0.05). Malaria knowledge of caregivers was significantly associated with the use of insecticide treated nets (ITNs) by children and sleeping conditions (p<0.05). Gender of caregiver (AOR = 4.47, 95% CI = 1.41 – 14.18, p<0.01), Education level (Primary; AOR = 3.34, 95% CI = 1.28 – 8.69, p<0.01 and Secondary; AOR = 12.44, 95% CI = 3.99 – 38.83, p<0.001) and Occupation (Farming; AOR = 0.33, 95% CI = 0.11 – 0.93, p<0.05) were predictors of malaria knowledge. Conclusion: Plasmodium falciparum still remain the prevalent species causing malaria in children. Majority of the caregivers had adequate knowledge about malaria. Despite this (adequate knowledge), caregivers’ attitudes and practices regarding malaria prevention and control in children were poor.
Thesis (MPH)
Keywords: Plasmodium; Species Infections; Yendi Municipal; Hospital; Northern Region